The degree of possession of scientific research skills among governmental school teachers in The Governorate of Batinah South in The Sultanate of Oman from their perspective - Al-Somsami, Rashid Suleiman Rashid; Al-Thohli, Hilal Shamis Hamad; Al-Shukeer, Mohamed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of possession of scientific research skills among public school teachers in Batinah South Governorate in the Sultanate of Oman from their perspectives, and the effect of the variables (gender, years of experience) on their responses. The researchers used the descriptive survey method by constructing a questionnaire consisting of 30 items and divided into four domains. The sampling of the was chosen as a stratified random sample and applied to of (160) male and female teachers. The results of the study revealed that the degree of teachers’ possession of scientific research skills got an overall average (3.28 out of 5), i.e. with a grade (medium), and at the level of the domains; whereas, the skills of the research plan got the highest average (3.43) with a grade of (significant), then the skill of presenting and discussing the results of the study with an average of (3.32) and thirdly; writing and documenting the research with an average of (3.28). Finally, the statistical analysis with an average of (2.90), all with a grade (medium). The results also showed that there were no statistically significant differences at the significance level of 0.05 due to the variables of gender and years of experience.The researchers recommended that; increasing the efforts of training centers in the governorates in implementing workshops and training courses concerned with scientific research, inclusion of the idea of scientific research as a teacher promotion project by the Ministry of Education. In addition to two proposals for future studies on the subject.
Keywords: possession degree; Scientific research skills; government schools; Batinah South Governorate; teachers